2020
DOI: 10.1186/s40104-020-00447-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inbreeding and identification of regions under heavy selection based on runs of homozygosity in a Large White pig population

Abstract: Background: Runs of homozygosity (ROHs) are homozygous segments of the genome where the two haplotypes inherited from the parents are identical. The current availability of genotypes for a very large number of single nucleotide polymorphisms (SNPs) is leading to more accurate characterization of ROHs in the whole genome. Here, we investigated the occurrence and distribution of ROHs in 3,692 Large White pigs and compared estimates of inbreeding coefficients calculated based on ROHs (F ROH), homozygosity (F HOM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 57 publications
(68 reference statements)
6
39
0
Order By: Relevance
“…LIF has two previously studied polymorphisms, one of which had a significant additive effect on number of piglets born alive in German Large White (Spötter et al, 2009 ). GAL3ST1 was detected in an ROH hotspot in Large White (Shi et al, 2020 ) and is hypothesized to be involved in spermatogenesis (Suzuki et al, 2010 ). In the same genomic region, we also found INPP5J (inositol polyphosphate-5-phosphatase J) and PLA2G3 (phospholipase A2 group III), which are associated with two type of fatty acids (docosahexaenoic acid and n-3 polyunsaturated fatty acid) in Large White (Zappaterra et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…LIF has two previously studied polymorphisms, one of which had a significant additive effect on number of piglets born alive in German Large White (Spötter et al, 2009 ). GAL3ST1 was detected in an ROH hotspot in Large White (Shi et al, 2020 ) and is hypothesized to be involved in spermatogenesis (Suzuki et al, 2010 ). In the same genomic region, we also found INPP5J (inositol polyphosphate-5-phosphatase J) and PLA2G3 (phospholipase A2 group III), which are associated with two type of fatty acids (docosahexaenoic acid and n-3 polyunsaturated fatty acid) in Large White (Zappaterra et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Runs of homozygosity (ROH)-based inbreeding coefficient (F ROH ) that was measured by the ratio of the total length of ROH to the length of autosomes (2.45 Gb in this study; Mcquillan et al, 2008). ROHs were identified for each individual using PLINK v 1.9 (Purcell et al, 2007) with the following parameters (Shi et al, 2020;Xie et al, 2019): (a) The minimum number of SNPs in a sliding window was 50; (b) the minimum ROH length was set to 1 Mb to eliminate the impact of strong linkage disequilibrium; (c) each ROH need contain a minimum of 80 consecutive SNPs, which was calculated by following equation (Lencz et al, 2007), an indicative of ancestral (more than 10 generations), middle (5 to 10 generations), and recent (within 5 generations) inbreeding, respectively (Mastrangelo et al, 2016).…”
Section: Inbreeding Coefficientmentioning
confidence: 99%
“…In that respect, the need for specific phenotypes has led to similar selective pressures on different domesticated breeds, whereas the genes under selection varied significantly among them 2 . Thus, various studies on SNP data have been performed within or across pig breeds in order to determine regions harboring these genes under potential selection for favored traits [3][4][5][6][7][8][9][10] . It was demonstrated that particularly the detection of homozygous stretches along the genome, designated as runs of homozygosity (ROHs), displayed an effective approach to target functionally important regions as well as to elucidate demography of populations and genetic diversity 4,5 .…”
Section: Selection For Desirable Traits and Breed-specific Phenotypesmentioning
confidence: 99%
“…It was demonstrated that particularly the detection of homozygous stretches along the genome, designated as runs of homozygosity (ROHs), displayed an effective approach to target functionally important regions as well as to elucidate demography of populations and genetic diversity 4,5 . ROH regions (ROHR) were found to give evidence for regions of strong directional selection for biological pathways related to desirable phenotypes like coat color and type, fertility, muscle and fat development, growth and metabolism 8,9,[11][12][13][14] significantly characterizing pig breeds.…”
Section: Selection For Desirable Traits and Breed-specific Phenotypesmentioning
confidence: 99%